Effects of acute exercise on fear extinction in rats and exposure therapy in humans: Null findings from five experiments. (August 2017) - Jacquart, Jolene; Roquet, Rheall F.; Papini, Santiago; Powers, Mark B.; Rosenfield, David; Smits, Jasper A.J.; Monfils, Marie-H.
Highlights: Acute exercise did not facilitate fear extinction learning or memory in rats. Acute exercise prior to extinction did not affect relapse in fear responding. Exercise prior to exposure therapy did not enhance its efficacy for fear of heights. Abstract: Background: Exposure therapy is an established learning-based intervention for the treatment of anxiety disorders with an average response rate of nearly 50%, leaving room for improvement. Emerging strategies to enhance exposure therapy in humans and fear extinction retention in animal models are primarily pharmacological. These approaches are limited as many patients report preferring non-pharmacological approaches in therapy. With general cognitive enhancement effects, exercise has emerged as a plausible non-pharmacological augmentation strategy. The present study tested the hypothesis that fear extinction and exposure therapy would be enhanced by a pre-training bout of exercise. Methods: We conducted four experiments with rats that involved a standardized conditioning and extinction paradigm and a manipulation of exercise. In a fifth experiment, we manipulated vigorous-intensity exercise prior to a standardized virtual reality exposure therapy session among adults with fear of heights. Results: In experiments 1–4, exercise did not facilitate fear extinction, long-term memory, or fear relapse tests. In experiment 5, human participants showed an overall reduction in fear of heights but exercise did not enhance symptom improvement. Conclusions: Although acute exercise prior to fear extinction or exposure therapy, as operationalized in the present 5 studies, did not enhance outcomes, these results must be interpreted within the context of a broader literature that includes positive findings. Taken all together, this suggests that more research is necessary to identify optimal parameters and key individual differences so that exercise can be implemented successfully to treat anxiety disorders.